UPAYA MENINGKATKAN MINAT BELAJAR SISWA MENGGUNAKAN MEDIA PEMBELAJARAN EDUCAPLAY PADA MATA PELAJARAN MATEMATIKA KELAS IV SD NEGERI KALIKOTES PURWOREJO - Lestari Agustin, Chita; Suryantari, Hadna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
At Kalikotes Public Elementary School, the goal of this research was to see how the integration of Educaplay affected the effectiveness of instruction and increased fourth-grade students' enthusiasm for mathematics. Educaplay is an interactive, game-based learning platform designed to enhance the fun and interactivity of the learning process. The Classroom Action Research (CAR) technique, specifically the Kemmis and McTaggart framework, was used in this study. It was carried out over two cycles, each of which included four stages: planning, implementation, observation, and evaluation. Data were gathered through a survey measuring students' interest in studying and observation forms that concentrated on the interactions between instructors and students. There were 22 pupils in all. The data were analyzed qualitatively and quantitatively using a descriptive approach. The average score increased from 25 (39%) during the pre-cycle stage to 65 (63%) in the first cycle and 88 (85%) in the second cycle, indicating a consistent improvement in the execution of learning activities. In addition, the students' interest in learning grew favorably, rising from 54% (very low) in the first phase to 72% (moderate) in the first cycle and 83% (good) in the second. These findings suggest that incorporating Educaplay into math lessons promotes a more successful learning experience and greatly boosts student participation.